2022
DOI: 10.3389/fimmu.2022.909932
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of LPAR5+ macrophages in osteosarcoma tumor microenvironment predicts better outcomes

Abstract: IntroductionTumor microenvironment (TME) has been shown to be extensively involved in tumor development. However, the dynamic change of TME components and their effects are still unclear. Here, we attempted to identify TME-related genes that could help predict survival and may be potential therapeutic targets.MethodsData was collected from UCSC Xena and GEO database. ESTIMATE and CIBERSORT algorithms were applied to estimate the components and the proportions of TIICs in TME. We analyzed the gene expression di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The TME remodelling‐related gene LPAR5+ is highly expressed in macrophages 123 and associated with tumour metastasis, according to He et al. GSEA analysis by Zhou et al.…”
Section: Intercellular Communication Between Os Cells and Other Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TME remodelling‐related gene LPAR5+ is highly expressed in macrophages 123 and associated with tumour metastasis, according to He et al. GSEA analysis by Zhou et al.…”
Section: Intercellular Communication Between Os Cells and Other Cellsmentioning
confidence: 99%
“…The TME remodelling-related gene LPAR5+ is highly expressed in macrophages 123 and associated with tumour metastasis, according to He et al GSEA analysis by Zhou et al also found that proinflammatory TME can transform into anti-inflammatory M2-TAMs enriched with the TGF-β and Hedgehog signalling pathways, bridging the dynamic transformation into the anti-inflammatory phenotype M2. In lung metastases, M3-TAMs or FABP4+ TAMs, the alveolar macrophages, could also shape the proinflammatory TME.…”
Section: Myeloidsmentioning
confidence: 99%